Potential Third-party Radiation Exposure from Patients Undergoing Therapy with 131I for Thyroid Cancer or Metastases. Issue 3 (March 2015) - D'Alessio, Daniela; Giliberti, Claudia; Benassi, Marcello; Strigari, Lidia
<x xml:space="preserve">Abstract</x> Abstract The purpose of this work is to evaluate the potential third-party radiation exposure from patients undergoing therapy with 131I for ablation of residual thyroid tumor or metastases, based in part on serial measurements of exposure rates. Exposure rate measurements were performed at 1 m and 5 cm from the surface of each treated patient until patient release. Dose estimates based on measured exposure rates were compared with those based on analytic point-source (PSM) and line-source (LSM) models. Effective doses D(∞) to travelers, co-workers and sleeping partners were estimated by using the standard gamma factor (Γ) and the physical half-life or the values derived from measured data. Seven hundred ten patients were studied until the exposure at 1 m was below the constraints of 0.010 mSv. The 131I activities administered ranged from 1.85 to 11.0 GBq (median: 3.7 GBq), according to the therapeutic requirements. Based on the PSM and an experimental Γ, the mean/maximum estimated D(∞) to sleeping partners, partners, travelers, and co-workers were 2.60/20.65, 0.32/2.53, 0.96/7.59, and 0.57/4.50 mSv, respectively. Using the LSM and an experimental Γ, the D(∞) values were 2.41/19.15, 0.32/2.50, 0.83/6.62, and 0.57/4.42 mSv, respectively, while they were almost double using the theoretical Γ. The results presented, based on measured data in a large cohort of 131I-treated thyroid cancer patients, will allow more accurate estimation of potential third-party D(∞) following patient release and thus may be used to better inform physicians and hospital staff on recommendations for patient release and post-release precautions following radioiodine therapies.